2011
DOI: 10.1152/ajpheart.01316.2010
|View full text |Cite
|
Sign up to set email alerts
|

An association between vasomotion and oxygen extraction

Abstract: Vasomotion is defined as a spontaneous local oscillation in vascular tone whose function is unclear but may have a beneficial effect on tissue oxygenation. Optical reflectance spectroscopy and laser Doppler fluximetry provide unique insights into the possible mechanisms of vasomotion in the cutaneous microcirculation through the simultaneous measurement of changes in concentration of oxyhemoglobin ([HbO(2)]), deoxyhemoglobin ([Hb]), and mean blood saturation (S(mb)O(2)) along with blood volume and flux. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 56 publications
(54 reference statements)
4
42
0
2
Order By: Relevance
“…The average values of C m and C th were 6.24 ± 0.06% and 0.211 ± 0.008%, respectively, in pre-occlusion (normal), which are close to typical values for Japanese subjects reported in the literatures [10,21,22]. The average value of 44.3 ± 3.4% for StO 2 in pre-occlusion agrees with the mean blood oxygen saturation of normal human subjects (range 30.2-52.4%) reported in the literatures [23]. During cuff occlusion, C oh and C dh decreased and increased, respectively.…”
Section: Estimating Chromophore Concentrations From the Cmcs Spectrumsupporting
confidence: 89%
“…The average values of C m and C th were 6.24 ± 0.06% and 0.211 ± 0.008%, respectively, in pre-occlusion (normal), which are close to typical values for Japanese subjects reported in the literatures [10,21,22]. The average value of 44.3 ± 3.4% for StO 2 in pre-occlusion agrees with the mean blood oxygen saturation of normal human subjects (range 30.2-52.4%) reported in the literatures [23]. During cuff occlusion, C oh and C dh decreased and increased, respectively.…”
Section: Estimating Chromophore Concentrations From the Cmcs Spectrumsupporting
confidence: 89%
“…Vasomotion is a form of spontaneous localized oscillations induced by spontaneous contraction and relaxation of the smooth muscle components in the small blood vessel walls which generate rhythmic changes in their diameter. Although vasomotion mechanisms are still under debate [12], several studies demonstrated that vasomotion may have beneficial effects on tissue oxygenation [13], [14], [15]. Therefore the hypothesis of a reduced muscle microvascular oxygenation in SCD patients, due to abnormal hemorheology, compensated by a greater vasomotion activity needs to be tested.…”
Section: Introductionmentioning
confidence: 99%
“…Since flow motion has predominantly been observed in participants with a skin temperature above 29.38C [3], the laser-Doppler probe was set at 308C. The LDF output was recorded for 25 min with a sample rate of 32 Hz, which gives a semi-quantitative assessment of skin microvascular blood perfusion expressed in arbitrary perfusion units (i.e.…”
Section: Skin Microvascular Flow Motion Measurementsmentioning
confidence: 99%
“…In fact, these rhythmic oscillations regulate microvascular flow distribution so that various tissue regions are intermittently perfused [1,2]. Indeed, theoretical and experimental studies demonstrate that an increase in vasomotion can increase total blood flow by 40-60% [3,4]. In addition, when active and passive vessels with the same average diameter are compared, active vessels have a lower vascular resistance (according to Poiseuille's law) [5,6], that is, vasomotion decreases arterial pressure by 20% [7].…”
Section: Introductionmentioning
confidence: 99%